BRAND IMAGE, KUALITAS PRODUK, MINAT BELI DAN KEPUTUSAN PEMBELIAN - Meyzi Heriyanto, Ogi Rifansyah, Okta Karneli, (Jurnal Ilmu Administrasi Negara, 2019)
Brand Image, Product Quality, Purchase Interests and Purchasing Decisions. Thepurpose of this study is to determine the brand image, product quality, buying interest andpurchasing decisions. The number of respondents as many as 90 people were randomly drawnfrom the population. Data collection techniques are questionnaires from the results of data analysiswhich include outer models, convergent validity, discriminant validity, composite reliability,average variance extracted, and inner models show that brand image and product quality have aninfluence on buying interest and purchasing decisions for MPV types of Suzuki brands. Ertiga atPT. Sejahtera Buana Trada Pekanbaru with a value of 0.75 means that the i nfluence of brandimage variables and product quality on buying interest and purchasing decisions is 75%. Theresults of hypothesis testing found that the f-count is greater than the f-table which means that Hais accepted.